Faire faire ou faire avec ? - Christine Martin; Christine Noël Lemaitre
The manager's function consists in getting others to do things. Thus, the manager is above all the one who must "take charge", i.e. motivate, control and supervise the activity of his team members. As the bearers of organizational modes and responsible for their implementation, managers can find themselves victims of these models and sometimes suffer from psychosocial risks. In this context, isn't it time to imagine a management style that does not overlook work, but that really understands it and starts from the real work of the different protagonists? Is this possible? And how can we think about managerial work itself? This contribution proposes a new conception of management integrating the analyses formulated by the French-speaking critical approaches developed by researchers in the human and social sciences, analyses taken up and extended by ergology. Indeed, the vision of work carried by ergology induces an alternative vision of management, which would no longer imply simply "making others do it" but rather "doing it with others", i.e. co-constructing the meaning to be given to one's work, to the organization to which one belongs and to living together. After having proposed a brief history of management with regard to the critical works devoted to management, we will explain how the ergological approach makes it possible to found a new approach to management. Then, we will see how this new approach consisting in "doing with" would bring elements of response in terms of health at work for the employees as well as for the managers themselves. We will propose a renewal of the function of the managers who must pass from doing to the ambition of "doing with".